UPAYA GURU PAI DALAM MENCEGAH BULLYING DI SMA NEGERI 2 PARE - Kunaenih Kunaenih; Firdaus Firdaus; Nadiah Nadiah (Almarhalah | Jurnal Pendidikan Islam, 2022)
AbstractThis research is motivated by the increase in cases of bullying which has recently been rife, bullying that occurs is not only done directly, both verbally and non-verbally. It has even happened in cyberspace through hate speech conveyed through social media. The problems in this research are; 1) What are the efforts of the PAI teacher at SMA Negeri 2 Pare in overcoming the problem of bullying at school?, 2) what are the factors that support and hinder teachers' efforts to prevent bullying at school?, 3) What methods do teachers use to prevent bullying in schools? . SMA Negeri 2 Pare is one of the favorite schools located in Pare sub-district, Kediri district. The purpose of this study was to determine the teacher's efforts to prevent bullying in schools. The research method used in this research is a case study with a qualitative approach, with key informants consisting of the principal, vice principal, teachers and students. The results of the study are: 1). By strengthening character education, 2). Increase the sense of Nationalism, 3). Increase the sense of religiosity, 4). Maintaining local culture as a student area in the character of students. Keywords: Effort, Teacher, Prevent Bullying